Compositional analysis of Gothic architecture in Europe and Ukraine - Hots, Anna; Rudenko, Leonila (Видавництво Львівської політехніки, 2013)
The article carried the compositional analysis of Gothic architecture in Europe, namely France, Italy and Germany. The authors investigated and compared patterns in proportions for example Ukrainian gothic cathedral and churches of Western Europe.
Keywords: cathedral; proportions; equilateral triangle; rectangular; Lviv architecture